The existential status of the meaning of human life - Manushak A. Egikyan (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The world of the present is quite complex and contradictory, having become transparent and fragile. The society described with the prefix «post» has exacerbated the problem of the essence of man, putting on the agenda the question of the posthuman in the projection of the «improvement» of man by technological know-how. In socio-philosophical discourse, the concept of the posthuman, with all its multivariate readings, brings to the fore the theme of the preservation of man and humanity as a whole. Homo sapiens, caught in the networks of a global techno-project to create an artificial world / intelligence / body, thinks about the limits of its boundlessness and the search for humanity, which is impossible to understand the meaning of human life. The eternal debate about the true nature of the meaning of life continues through the ages. Thinkers from different schools and different eras offer their explanations of this issue. The radical among them reject the very idea of the significance of the meaning of life, while others, on the contrary, recognize it, but insist on the negative side, while others associate it with positive aspects. However, the central task of each person remains the multifaceted development of himself as a person. This, in turn, ensures a person's contribution to the social and historical course of events, designating it as a personal vocation and life goal. Existential thinking provides an opportunity to re-evaluate a social phenomenon as something metaphysical and holistic, reading it through the prism of social action. Here, the idea of social realization as a significant act is embedded in the understanding of the phenomenon.